Pengaruh Pemberian Peregangan Otot (Stretching)Terhadap Keluhan Muskuloskeletal Dan Kejenuhan PadaPekerja Bagian Menjahit Divisi GarmentDi Pt. Tyfountex Indonesia SukoharjoTahun 2016 - Anggriawan, Ronny, Sri Darnoto, SKM., MPH (2016)
Sewing work is monotonous jobs with working attitude sitting in a long time. Work attitude is unnatural for work and monotonous work can lead to musculoskeletal disorders and saturation of the workers. This research aims to know the effects of giving muscle stretching towards the musculoskeletal complaints and saturation of the sewing labors of garment division at PT. Tyfountex Indonesia Sukoharjo. This research method using Quasi alphabets experiment with non equivalent control group design. The research sample is 30 people-sex women by using purposive sampling that meet the criteria for inclusion. Statistical tests using Mann Whitney U. The results of statistical tests to influence the awarding of muscle stretching (stretching) of musculoskeletal complaints and burnout on the part of the workers sew the garment Division, both the p-value obtained to the same value (0.00 ≤ 0.05). A summary of this research an significant effects of giving muscle stretching towards the musculoskeletal complaints and saturation of the sewing labors of garment division at PT. Tyfountex Indonesia Sukoharjo